Prevalence and impact of long COVID-19 among patients with diabetes and cardiovascular diseases in Bangladesh - Sharif, Nadim; Sharif, Nazmul; Khan, Afsana; Halawani, Ibrahim F.; Alzahrani, Fuad M.; Alzahrani, Khalid J.; Díez, Isabel De la Torre; Vargas, Debora Libertad Ramírez; Castilla, Angel Gabriel Kuc; Parvez, Anowar Khasru; Dey, Shuvra Kanti (Frontiers in Public Health, 2023)
Co-prevalence of long-COVID-19, cardiovascular diseases and diabetes is one of the major health challenges of the pandemic worldwide. Studies on long-COVID-19 and associated health outcomes are absent in Bangladesh. The main aim of this study was to determine the prevalence and impact of long-COVID-19 on preexisting diabetes and cardiovascular diseases (CVD) on health outcomes among patients in Bangladesh. We collected data from 3250 participants during 01 January, 2023 to 30 March, 2023 in Bangladesh, retrospectively. Multivariable logistic regression model was used to determine the odds ratio between independent and dependent variables. Kaplan-Meier survival curve was used to determine the cumulative survival. COVID-19 was detected among 73.4% (2385 of 3250) participants. Acute long-COVID-19 was detected among 28.4% (678 of 2385) and chronic long-COVID-19 among 71.6% (1707 of 2385) patients.CVD and diabetes were found among 32%, and 24% patients, respectively. Mortality rate was 18% (585 of 3250) among the participants. Co-prevalence of CVD, diabetes and COVID-19 was involved in majority of fatality (95%). Fever (97%), dry cough (87%) and loss of taste and smell (85%) were the most prevalent symptoms. Patients with co-prevalence of CVD, diabetes and COVID-19 had higher risk of fatality (OR: 3.65, 95% CI, 2.79-4.24). Co-prevalence of CVD, diabetes and chronic long-COVID-19 were detected among 11.9% patients. Risk of hospitalization and fatality reduced significantly among the vaccinated. This is one of the early studies on long-COVID-19 in Bangladesh.